2021
DOI: 10.3390/microorganisms9071449
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of the Fecal but Not Salivary Microbiome in Patients with Behçet’s Disease According to Disease Activity Shift

Abstract: The human microbiome plays an important role in various diseases, including Behçet’s disease (BD). However, the effects of disease activity and covariates influencing the microbial composition have not yet been investigated. Therefore, we investigated the fecal and salivary microbiomes of BD patients compared to those of recurrent aphthous ulcer (RAU) patients, as well as dietary habit-matched healthy controls (HCs) selected from immediate family members using 16S rRNA gene sequencing. The fecal microbiome alp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 46 publications
1
7
0
Order By: Relevance
“…After performing 16s rDNA sequencing of fecal samples, we observed signifcantly decreased microbial diversity in individuals with acne vulgaris, which then increased to health levels after three months of the metformin therapy. A decreased diversity in gut microbiota in patients with acne and other infammatory skin diseases, such as Behçet's disease and psoriasis, was also reported in previous studies [25,26]. It has been reported that individuals who have low bacterial richness have a more pronounced infammatory phenotype [27].…”
Section: Discussionsupporting
confidence: 69%
“…After performing 16s rDNA sequencing of fecal samples, we observed signifcantly decreased microbial diversity in individuals with acne vulgaris, which then increased to health levels after three months of the metformin therapy. A decreased diversity in gut microbiota in patients with acne and other infammatory skin diseases, such as Behçet's disease and psoriasis, was also reported in previous studies [25,26]. It has been reported that individuals who have low bacterial richness have a more pronounced infammatory phenotype [27].…”
Section: Discussionsupporting
confidence: 69%
“…In 22 individuals with Behcet’s, a significant depletion in the genera Roseburia and Subdoligranulum , two Clostridium clusters, was found when compared with 16 healthy controls 7. Yet in another study involving nine individuals with Behcet’s, the abundance of Bacteroides uniformis was significantly higher than in 9 healthy controls, but the significant bacterial differences found in the first study were not demonstrated 33. Finally, in a study involving 35 individuals who underwent allogeneic haematopoietic stem cell transplantation, patients microbiomes were sampled at the time of acute (aGVHD) onset and compared with 35 post-transplant individuals without GVHD.…”
Section: Methodsmentioning
confidence: 82%
“… 7 Yet in another study involving nine individuals with Behcet’s, the abundance of Bacteroides uniformis was significantly higher than in 9 healthy controls, but the significant bacterial differences found in the first study were not demonstrated. 33 Finally, in a study involving 35 individuals who underwent allogeneic haematopoietic stem cell transplantation, patients microbiomes were sampled at the time of acute (aGVHD) onset and compared with 35 post-transplant individuals without GVHD. Interestingly, specific microbiome signatures were associated with gastrointestinal aGVHD severity.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some cross-sectional studies have reported that gut bacterial abundance changes in BD patients compared with healthy controls ( Table 3 ) ( Consolandi et al., 2015 ; Shimizu et al., 2016 ; Ye et al., 2018 ; Oezguen et al., 2019 ; Shimizu et al., 2019 ; Bilge et al., 2020 ; Tecer et al., 2020 ; van der Houwen et al., 2020 ; Kim et al., 2021 ). These results showed that the gut microbiota in BD patients was enriched with lactic acid-producing bacteria, sulfate-reducing bacteria, and some opportunistic pathogens but lacked butyric acid-producing bacteria and methanogenic bacteria.…”
Section: Variable-vessel Vasculitismentioning
confidence: 99%